EFFECT OF NINE WEEKS OF SAQ TRAINING PROGRAMME ON SELECTED BIO MOTOR ABILITIES OF MALE KHO-KHO PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to investigate the effect of SAQ training for nine week on selected biomotor abilities (speed, agility and explosive power) of male kho-kho players. To achieve this 30 male kho-kho players were selected randomly from Department of Physical Education and Sports Sciences, SK University,Anantapuram. The selected subjects were assigned to 2 groups: SAQ training group (n=15) and control group (n=15). Speed, explosive power and agility were selected as criterion variables and tested by 50 meters sprint, standing broad jump test and 505 agility - test. The duration of the training prescribed in this study was nine weeks was carried out during preparatory phase. Pre and post data was measured on the indoor. The data was analyzed by applying Analysis of Covariance (ANCOVA) technique to find out the effect of SAQ training on selected biomotor ability of kho-kho players. The level of significance was set at 0.05. The adjusted post test means showed significance on speed [F (1, 25) = 10.82, p < 0.003], explosive power [F (1, 23) = 32.84, p < 0.000] and agility [F (1, 23) = 42.83, p < 0.000] indicating that SAQ training significantly improved the speed, explosive power and agility of kho-kho players compared to Control group. Improvement in SAQ training group was noticed in speed, explosive power and agility of male kho-kho players.